Sinergisitas Kepemimpinan Kepala Madrasah Dan Komite Sekolah Berbasis Prinsip Kolegalitas Islami - Edi Wardani; Sukandar Hadi; Tabrani; Masruri; Zaharudin (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
This study aims to develop a conceptual model of Synergistic Leadership between Madrasah Principals and School Committees Based on Islamic Collegiality Principles as an alternative approach to strengthening madrasah governance and improving educational quality. This study employed a qualitative approach using a library research method through a systematic synthesis of relevant academic literature on educational leadership, collaborative leadership, school governance, and Islamic leadership. Data analysis was conducted through thematic identification, conceptual categorization, and integration of previous research findings to construct a contextual framework for Islamic educational institutions. The findings reveal that leadership synergy between madrasah principals and school committees is formed through five main components: shared vision, strategic communication and coordination, participatory decision-making, shared accountability, and partnership networking. This study introduces the concept of Islamic Collegiality as a new framework that integrates the principles of syūrā (consultation), amanah (trust and responsibility), ‘adl (justice), mas’uliyyah (moral accountability), and ta‘āwun (cooperation) as the foundation of leadership relationships between madrasah principals and school committees. This model expands the perspective of collaborative leadership by incorporating ethical, social, and spiritual dimensions that characterize Islamic education. The study contributes theoretically to the development of Islamic educational leadership studies and provides practical implications for strengthening madrasah governance that is participatory, transparent, accountable, and sustainable.